NURSING GUIDELINES FOR CARING FOR NEOPLASTIC WOUNDS DURING HOSPITAL DISCHARGE: INTEGRATIVE REVIEW - Gonçalves Pereira de Oliveira, Denise (2023)
Objective: To identify in publications the guidelines provided by nurses to patients and caregivers/relatives at hospital discharge on care for malignant neoplastic wounds. Methodology: This is an integrative review of the scientific production related to malignant neoplastic wounds in PUBMED, EMBASE, CINAHL and LILACS databases. Data collection was carried out in the period of January 2023 and, as inclusion criteria, full texts in Portuguese, English and Spanish were adopted, available in full in free access, published in the last ten years (2012 - 2022). Integrative literature review articles, dissertations, theses and books were excluded. Results: 235 articles were retrieved and two reviewers selected 171 studies, of which 108 were excluded by reading the abstracts, 63 studies were read in full and, in the end, 02 studies were included in this review. Conclusion: Through the analysis of the studies, it was noticed that the information, when provided to patients and caregivers/relatives, occurred predominantly verbally, without the use of any additional instrument that would facilitate the management of malignant neoplastic wounds for caregivers, relatives and patients at home